PENYELENGGARAAN PELATIHAN BLENDED LEARNING PADA PEMBELAJARAN DI RUMAH PINTAR NURUL FALAH KOTA BANDUNG - Nunu Heryanto; Oong Komar; Cucu Sukmana (Abdimas Siliwangi, 2021)
The very rapid changes in society as a result of the revolution in communication technology have made all areas of life more competitive. Likewise with the determination of learning innovations must be adjusted to the consideration of approaches in learning in order to produce quality Human Resources (HR). Therefore, especially in the conditions of Covid 19 which require the holding of distance learning, it is necessary to increase the competence of managers and students by applying information technology-based learning such as the blended learning model. This service aims to describe the implementation of a blended learning training program for learning at the Nurul Falah Smart House, Bandung. To reveal the data and information, the community service team conducted a blended learning training program on learning at the Nurul Falah Smart House, Bandung city by applying the lecture, question and answer, discussion, demonstration and brainstorming methods. The blended learning training system in its cycle is divided into three stages, namely, the planning, implementation and evaluation stages. In practice, it always begins with a needs analysis, then compiles a training design then develops blended learning training materials, conducts training and ends with an evaluation. The results of this training evaluation indicate an increase in the cognitive aspects of the training participants, an increase from before and after training.